How to save a life - Fenton, Liz; Steinke, Lisa (Lake Union Publishing, 2020)
Dom is having a very bad day--one he literally can't escape. When Dom bumps into Mia, his ex-fiancée whom he hasn't seen in almost a decade, he believes they've been given a second chance and asks her out. When Mia dies tragically on their date, Dom makes a desperate wish: to be given the chance to save her life. And when he wakes the next morning to the shock that she's alive, he thinks his wish may have been granted. But day after day, no matter what he changes about their time together, she still meets a terrible fate. Dom frantically searches for answers to save his beloved Mia and rekindle their former love. But the further he digs, the more obsessed he becomes, making him realize that slowing down time may be the only way to see things clearly. As he's forced to confront the truth about himself and those he's closest to, Dom vows that he'll watch Mia die a thousand times if it means he can save her once.